Acridine-decorated cyclometallated gold(iii) complexes: synthesis and anti-tumour investigations. Issue 38 (11th September 2018) - Williams, Morwen R. M.; Bertrand, Benoît; Fernandez-Cestau, Julio; Waller, Zoë A. E.; O'Connell, Maria A.; Searcey, Mark; Bochmann, Manfred
Abstract : (C^N) and (C^N^C) cyclometalated Au(iii ) represent a highly promising class of potential anticancer agents. Abstract : (C^N) and (C^N^C) cyclometalated Au(iii ) represent a highly promising class of potential anticancer agents. We report here the synthesis of seven new cyclometalated Au(iii ) complexes with five of them bearing an acridine moiety attached via (N^O) or (N^N) chelates, acyclic amino carbenes (AAC) and N-heterocyclic carbenes (NHC). The antiproliferative properties of the different complexes were evaluated in vitro on a panel of cancer cells including leukaemia, lung and breast cancer cells. We observed a trend between the cytotoxicity and the intracellular gold uptake of some representative compounds of the series. Some of the acridine-decorated complexes were demonstrated to interact with ds-DNA using FRET-melting techniques.